Pengaruh Posisi Lereng terhadap Sifat Fisika dan Kimia Tanah pada Inceptisols di Jatinangor - Mahfud Arifin; Novarina Darmawan Putri; Apong Sandrawati; Rachmat Harryanto (Fakultas Pertanian Universitas Padjadjaran, 2018)
ABSTRACT Slope held a vital role in soil formation and development through erosion, transportation, and deposition. The degree of the slope determines the flow rate and volume of surface water, while the slope position determines rate of the erosion. The research aimed to understand the impact of the slope position against physical (texture, Bulk Density, top soil thickness,) and chemical (pH, Organic carbon, and cation exchange capacity (CEC)) and the correlation between the top soil thickness to physical and soil chemical properties. The research was conducted in April to June 2016. The soil samples were taken from 15-25% slope and three positions: upper slope, middle slope and lower slope. Each slope was repeated 5 times, hence 15 spots of soil samples were obtained. This research used descriptive comparative method and stratified purpose sampling as the sampling technique. The results of T-Student test showed that the slope position influenced the topsoil thickness of 6.91 point in the upper and middle slope and 3.89 point in the middle and lower slope. The results of the correlation test in each parameter in the upper hill showed there was correlation between top soil against dust fraction (r=0.826), top soil against clay fraction (r=0.823), and top soil against soil CEC (r=0.787). The middle slope showed there was correlation between top soil and soil pH (r=0.872) and topsoil to soil CEC (r=0.790). The lower slope showed there was correlation between top soil and soil pH (r=0.870).Key words: soil erosion, Inceptisols, slope position, topsoil